Magnitude and Determinant Factors of Herbal Medicine Utilization Among Mothers Attending Their Antenatal Care at Public Health Institutions in Debre Berhan Town, Ethiopia - Wake, Getu Engida; Fitie, Girma Wogie (Frontiers in Public Health, 2022)
Background World health organization defined herbal medicines as the practice of herbs, herbal materials, herbal preparations, and finished herbal products. Globally women are the primary utilizer of herbal medicine and even they consume it during their pregnancy period. The World health organization reported that the majority of the global population used traditional medicine. This study aimed to assess the magnitude and determinant factors of herbal medicine utilization among pregnant mothers attending their antenatal care at public health institutions in Debre Berhan town, Ethiopia. Methodology Institution-based cross-sectional study was conducted among pregnant mothers who attended their antenatal care at public health institutions in Debre Berhan town, Ethiopia from 12 February 2021 to 12 April 2021. A systematic random sampling method was used to get selected pregnant mothers. Epi data version 3.1 and SPSS version 25 were used for data entry and analysis, respectively. P-value ≤0.05 was used as a cut point of statistical significance in multivariable binary logistic regression. Results A total of 422 pregnant mothers were included with a 100% response rate and 277 (65.6%) of them used an herbal medicine during their current pregnancy. Educational level up to primary school [AOR 2.21, 95% CI: 1.17 – 4.18], monthly family income of <2,800 ETB [AOR 1.72, 95% CI: 1.01–2.92], and lack of awareness of the complication of herbal medicine utilization [AOR 10.3, 95% CI: 6.27–16.92] were determinant factors of herbal medicine utilization. Conclusion The utilization of herbal medicine among pregnant mothers in this study is high and almost all of them did not disclose their utilization of herbal medicine to their healthcare providers. The ministry of health should integrate traditional medicine with conventional medicines. Midwives and obstetricians should openly discuss regarding benefits and complications of herbal medicine utilization for those pregnant mothers during their antenatal care counseling sessions as routine care.